Marketing research : methodological foundations - Churchill, Gilbert A.; Iacobucci, Dawn. (Mason, Ohio : Thomson/South-Western, 2005)
'Marketing Research: Methodological Foundations, 9E, has established itself as a classic through eight previous editions by presenting balanced coverage of both the qualitative and quantitative aspects of marketing research. The six stages of the research process provide a solid framework to ensure the development of students' conceptual and practical understanding of marketing research.''This text serves both the aspiring manager and the aspiring researcher through its basic organization around the stages of the research process. The research process is a sequence of steps that must be completed when answering a research question and the six parts of the text parallel these stages: Formulate the problem, determine the research design, design the data-collection methods and forms, design the sample and collect the data, analyze and interpret the data, and prepare the research report.''This new edition provides extensive treatment of cutting-edge topics such as data-mining, ethics in the field of marketing research, international marketing research, customer relationship management, and current managerial trends for effective decision-making in the field.''Cases are found at the end of each part to assist readers in developing their evaluation and analytical skills and also to help them apply the text materials to various marketing research situations. Some of the cases also include raw data for students to use with either SPSS or Excel.'--BOOK JACKET.
Includes bibliographical references and indexes.
Keywords: Marketing research